Prospective comparative multi-centre study on imported Plasmodium ovale wallikeri and Plasmodium ovale curtisi infections - Gerardo Rojo-Marcos (Malaria Journal, 2018)
Abstract Background Few previous retrospective studies suggest that Plasmodium ovale wallikeri seems to have a longer latency period and produces deeper thrombocytopaenia than Plasmodium ovale curtisi. Prospective studies were warranted to better assess interspecies differences. Methods Patients with imported P. ovale spp. infection diagnosed by thick or thin film, rapid diagnostic test (RDT) or polymerase chain reaction (PCR) were recruited between March 2014 and May 2017. All were confirmed by DNA isolation and classified as P. o. curtisi or P. o. wallikeri using partial sequencing of the ssrRNA gene. Epidemiological, analytical and clinical differences were analysed by statistical methods. Results A total of 79 samples (35 P. o. curtisi and 44 P. o. wallikeri) were correctly genotyped. Males predominate in wallikeri group (72.7%), whereas were 48.6% in curtisi group. Conversely, 74.3% of curtisi group were from patients of African ethnicity, whilst 52.3% of Caucasians were infected by P. o. wallikeri. After performing a multivariate analysis, more thrombocytopaenic patients (p = 0.022), a lower number of platelets (p = 0.015), a higher INR value (p = 0.041), and shorter latency in Caucasians (p = 0.034) were significantly seen in P. o. wallikeri. RDT sensitivity was 26.1% in P. o. curtisi and 42.4% in P. o. wallikeri. Nearly 20% of both species were diagnosed only by PCR. Total bilirubin over 3 mg/dL was found in three wallikeri cases. Two patients with curtisi infection had haemoglobin under 7 g/dL, one of them also with icterus. A wallikeri patient suffered from haemophagocytosis. Chemoprophylaxis failed in 14.8% and 35% of curtisi and wallikeri patients, respectively. All treated patients with various anti-malarials which included artesunate recovered. Diabetes mellitus was described in 5 patients (6.32%), 4 patients of wallikeri group and 1 curtisi. Conclusions Imported P. o. wallikeri infection may be more frequent in males and Caucasians. Malaria caused by P. o. wallikeri produces more thrombocytopaenia, a higher INR and shorter latency in Caucasians and suggests a more pathogenic species. Severe cases can be seen in both species. Chemoprophylaxis seems less effective in P. ovale spp. infection than in P. falciparum, but any anti-malarial drug is effective as initial treatment. Diabetes mellitus could be a risk factor for P. ovale spp. infection.